2021
DOI: 10.1186/s12874-021-01285-y
|View full text |Cite
|
Sign up to set email alerts
|

Intra-database validation of case-identifying algorithms using reconstituted electronic health records from healthcare claims data

Abstract: Background Diagnosis performances of case-identifying algorithms developed in healthcare database are usually assessed by comparing identified cases with an external data source. When this is not feasible, intra-database validation can present an appropriate alternative. Objectives To illustrate through two practical examples how to perform intra-database validations of case-identifying algorithms using reconstituted Electronic Health Records (rEHR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…22,23 Because this clinical event was not directly available in the database, we used a recently published specific algorithm based on hospital admissions and/or the use of corticosteroids (either oral or intravenous). 24-26…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Because this clinical event was not directly available in the database, we used a recently published specific algorithm based on hospital admissions and/or the use of corticosteroids (either oral or intravenous). 24-26…”
Section: Methodsmentioning
confidence: 99%
“…The event of interest was the occurrence of relapse which is usually defined as new symptoms or worsening of pre-existing symptoms for at least 24 hours and occurring at least 30 days after a previous relapse 22,23 . As this clinical event was not directly available in the database, we used a recently published specific algorithm based on hospital admissions and/or use of corticosteroids (either oral or intravenous) [24][25][26] .…”
Section: Relapses Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Thurin et al conclude that in the absence of an alternative, tabular patient profiles based on claims data ("reconstituted electronic health records") are a valuable tool for intra-database validation and performance estimation of case-identifying algorithms. 5 In fact, Thurin et al suggested specific conditions necessary for a successful validation process, which were satisfied in our study: "1) the health outcome of interest must be managed by a specific sequence of cares and encounters; and 2) the considered health-care database must capture in an exhaustive way a sufficient number of medical elements in line with the outcome of interest". Misclassification of outcomes might seriously bias study findings.…”
Section: Discussionmentioning
confidence: 70%
“…Patient profiles extracted from French claims data, ie, chronological tabular summaries of the relevant information available on a patient, have been shown to serve as an alternative to patient charts. 5 To date, no study has been published on using patient profiles extracted from German claims data for outcome validation.…”
Section: Introductionmentioning
confidence: 99%